Securitization of Intellectual Property: Legal Recourse in India (Journal of Intellectual Property Rights (JIPR), 2023)
Capital has been a major cause of concern amongst entrepreneurs across the globe. Not everyone enters the professionalsetting with a bag full of money, neither did the Ambani’s nor did the TATA group. It was not just investments into fruitbearingfunds but also loans that have made them superpowers in the market, today. A loan requires one to offer collateralagainst the principal amount, this collateral is often referred to as security in common parlance. We most often offer tangibleassets such as gold, land, car, etc. as security, however, can an intangible asset such as intellectual property also be offeredas bank security? This question is dealt with at length by the authors while discussing the legal discourse in India and otherdeveloped countries.The authors have collected insights from theearlier cases where intellectual property was offered assecurity (more specifically as collateral) and analyzed its legal implications in the long run.